2003
DOI: 10.1124/jpet.102.042622
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β2-Adrenergic Receptor Stimulation on Interleukin-18-Induced Intercellular Adhesion Molecule-1 Expression and Cytokine Production

Abstract: ␤-Adrenergic receptor (AR) agonists have been demonstratedto modulate the production of inflammatory mediators. Recent studies implied that ␤2-AR agonists might be useful for chronic inflammatory diseases caused by interleukin (IL)-18. In the present study, we found that norepinephrine, epinephrine, or isoproterenol down-regulated IL-18 (100 ng/ml)-induced intercellular adhesion molecule (ICAM)-1 expression on monocytes in a dose-dependent manner (10 Ϫ8 -10 Ϫ4 M), but did not effect B7.1 and B7.2 expression af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…*P Ͻ 0.05 vs. control mean, Dunnett's test. intercellular adhesion molecule-1 in leukocytes through a ␤ 2 -adrenergic receptor-mediated mechanism (34).…”
Section: Discussionmentioning
confidence: 99%
“…*P Ͻ 0.05 vs. control mean, Dunnett's test. intercellular adhesion molecule-1 in leukocytes through a ␤ 2 -adrenergic receptor-mediated mechanism (34).…”
Section: Discussionmentioning
confidence: 99%
“…We found that ␤2-AR stimulation inhibited IL-18-initiated IL-12, TNF-␣ and INF-␥ production [21], and that the stimulation of ␤2-AR suppressed LPS-induced production of TNF-␣, and T cell proliferation through inhibiting the cellto-cell interaction between monocytes and T cells [22]. The purpose of the present study is to investigate the effect of ␤2-AR stimulation on IL-18 production.…”
Section: Introductionmentioning
confidence: 96%
“…It was suggested that FMF may be related to abnormal catecholamine metabolism because in these subjects a significantly higher plasma dopamine β-hydroxylase (DBH) activity was found compared with controls (Barakat et al, 1988). These irregularities in catecholamines metabolism indicate that metaraminol markedly affected immune homeostasis of the host because abnormal stimulation of adrenergic and dopaminergic receptors can lead to modulation of the cytokine network and contribute to a wide range of pathology (Agarwal & Marshall, 2000;Kohm & Sanders, 2001;Bergmann & Sautner, 2002;Takahashi et al, 2003;Johnson et al, 2005;Kaneko et al, 2005).…”
Section: Metaraminolmentioning
confidence: 94%